A method for depositing polystyrene microspheres
By forming zinc oxide films on the substrate and combining with the vertical deposition method, the problem of polystyrene microspheres depositing on flexible curved substrates is solved, and its uniform deposition and mechanical performance improvement on multiple substrates is achieved.
Patent Information
- Application Number
- CN202211336560.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-10-28
AI Technical Summary
Polystyrene microspheres are difficult to deposit uniformly on flexible curved substrates, and the lack of support and adhesion causes shedding, limiting their application range.
The zinc oxide film is formed on the substrate by atomic layer deposition technology to enhance its hydrophilicity, and combined with the vertical deposition method, polystyrene microspheres can be uniformly deposited on a variety of substrates, including carbon nanotubes, electrospinning films, Carbon cloth, nickel foam and three-dimensional graphene, etc.
The uniform deposition of polystyrene microspheres on the curved substrate is achieved, which improves its mechanical properties and stability and expands its application range.
Abstract
Description
Technical Field
[0001] The invention relates to the field of atomic layer deposition, and in particular to a method for depositing polystyrene microspheres. Background Art
[0002] Monodisperse polystyrene (PS) microspheres are the most common type of polymer microspheres, prepared from styrene (St) as a monomer. They have the characteristics of small particle size, large specific surface area, good dispersion performance, good relative stability, easy modification and removal, and are widely used in the fields of biomedicine, building materials, photonic crystal preparation, and microelectronics technology. In addition, due to its easy removal characteristics such as immersion in organic solvents or calcination in air, polystyrene microspheres are also often used as a template material to construct porous, inverse opal, hollow and other complex structures, and have important industrial applications, including high catalytic performance sensing, catalysis and energy storage.
[0003] The vertical deposition self-assembly method is a simple, economical and thickness-controllable method for preparing photonic crystals. The principle is to immerse the substrate vertically in a suspension of monodisperse microspheres. After the suspension temperature is applied, the solvent begins to evaporate. In the meniscus at the junction of the solid, liquid and gas phases, the microspheres are driven by capillary forces to self-assemble into a periodic arrangement structure on the substrate surface. The key to the vertical deposition method is to control the relative movement rate between the substrate and the solution, that is, to achieve a better deposition effect by controlling the evaporation temperature of the solution. The thickness of the deposited microspheres can be precisely controlled by adjusting the diameter of the microspheres and the concentration of the solution. In order to ensure the normal vertical deposition, the substrate needs to have a certain hydrophilicity to ensure the formation of the meniscus, and finally ensure that the microspheres can be self-assembled at the meniscus and deposited on the substrate. At present, the substrates for vertical deposition are all flat, and it is impossible to deposit microspheres on curved substrates, because in places where the curvature of the substrate surface is relatively large, the microspheres will fall off from the curved substrate due to lack of support and gravity. Therefore, a suitable method is needed to modify the surface of the substrate so as to increase the bonding force between the substrate and the polystyrene microspheres.
[0004] Carbon nanotube fiber is composed of nano-scale carbon nanotubes as the basic assembly unit, and it is a macroscopic continuous fiber material with a diameter of micrometer level. According to literature reports, the single carbon tube structure and carbon tube micro-assembly structure in carbon nanotube fiber, such as the number of walls, aspect ratio, orientation, density, and inter-tube interaction, are key factors that determine the fiber force and electrical properties. In addition, due to its high strength, high conductivity, high toughness and other characteristics, it has a wide range of applications in aerospace, new energy vehicles, rail transportation and other fields.
[0005] Static spinning is a widely used technology for preparing nanofibers. The diameter of the prepared fibers ranges from a few nanometers to a few microns. The prepared fibers have the characteristics of high aspect ratio, large specific surface area, controllable pores and excellent mechanical properties. The electrospinning device consists of a high-voltage power supply, a syringe, a propulsion pump, a collector and a needle. The specific working principle is as follows: when the device is electrospinning, the positive electrode of the high-voltage power supply is connected to the needle, and the negative electrode of the high-voltage power supply is connected to the collector and grounded. At this time, the solution squeezed from the needle by the syringe and the propulsion pump is charged under high pressure, forming an electrostatic repulsion opposite to the surface tension. The filaments formed by the droplets are further stretched to form a cone, and a fine jet will be formed at the bottom of the cone. Under the action of the electric field and solvent volatilization, the jet forms extremely fine fibers that are wrapped around the rotating collector surface. Among them, the factors affecting film formation are: the molecular weight of the polymer molecules that make the solution, the solution concentration, the voltage, the collection distance, the feed rate and the needle setting.
[0006] Carbon cloth is a kind of carbon fiber fabric made by carbonization calcination or carbon fiber weaving of pre-oxidized polyacrylonitrile (PAN) fiber fabric. The main component of the substrate is carbon, usually greater than 99wt%. It has a series of excellent properties such as high strength, low density, good creep resistance, flexible processability, chemical stability and thermal stability, that is, high durability, low thermal expansion coefficient and high electrical conductivity. Therefore, it is widely used in the fields of electrochemistry, lithium batteries, supercapacitors and fuel cells, etc. However, since the surface of the substrate is non-polar, it has no affinity for polar molecules (water), and various additives will adhere to the surface of the substrate and accumulate dust during production and transportation, which will make it weakly hydrophobic. Therefore, its application in polar solvent systems is limited. Therefore, in actual operation, it is often necessary to hydrophilize the surface of the substrate, such as heat treatment oxidation, electrochemical treatment, liquid phase treatment, plasma treatment and process control methods for increasing oxygen-containing functional groups on the surface of the substrate.
[0007] Nickel foam is made of nickel metal in the shape of a foam sponge. It has a three-dimensional fully through mesh structure and a porosity of up to 96-98%. Compared with the metal of the same volume, the surface area of nickel foam can reach 6-10 times. In addition, the three-dimensional gaps also have the functions of filtering and maintaining the flow stability of gases and fluids. In addition, nickel foam can be cut, bent, and simply pasted. It has strong thermal conductivity and maintains the excellent properties of the original nickel. Therefore, nickel foam has a wide range of applications such as battery electrode materials, fuel cells, catalytic carriers, heat dissipation, etc.
[0008] Three-dimensional (3D) graphene refers to a two-dimensional (2D) graphene assembly with a three-dimensional structure. Graphene itself is a single-layer two-dimensional carbonaceous material formed by tightly stacked carbon atoms, with excellent mechanical, electrical conductivity, optical and other properties. The three-dimensional structure of graphene gives it more excellent properties, such as flexibility, porosity, and high specific surface area due to porosity, making it have broader application prospects in many fields such as energy storage (supercapacitors, lithium-ion battery materials), catalysis, environmental protection and flexible conductive materials.
[0009] 3D printing technology, also known as additive manufacturing, is a technology that uses digital model files as the basis, and uses bondable materials such as metal powder or plastic to construct objects by printing layer by layer. The materials for polymer 3D printing include thermoplastic wires, powders, and a small amount of photosensitive polymers. Its application range is very wide, such as creating lightweight complex structures in aerospace, architectural structure models, art replicas, and biological tissues and organs. Among them, the substrate manufactured by metal 3D printing is the most outstanding among all 3D printing technologies in terms of strength and durability. Therefore, depositing polystyrene microspheres on 3D printing substrates including metal, polymer and inorganic substrates is conducive to further expanding the application of polystyrene microspheres.
[0010] Atomic layer deposition (ALD) is a precise conformal deposition technology for ultra-thin films with angstrom-level thickness control at low temperatures. ALD is a technology similar to chemical vapor deposition (CVD) that grows thin films through repeated cycles. Each cycle includes 2 or more "half reactions" separated by inert gas cleaning and pumping. The "half reactions" are self-limiting, so the amount of added material can be precisely controlled. The film formed by depositing the material on the surface of the substrate layer by layer in the form of a single atomic film by atomic layer deposition has a uniformity controllable at 0.1nm. Common depositable materials include superconducting materials, conductors, semiconductors, oxides, single-element materials, etc. Due to the advantages of good uniformity, high conformality, and high purity of the atomic layer deposition process, it has been widely used in the semiconductor industry, capacitors, lithium-ion batteries, sensor technology, micro-electromechanical systems, etc. Therefore, the atomic layer deposition method was selected to modify the surface of the substrate on which the polystyrene microspheres were deposited. After repeated experiments, it was known that atomic layer deposition of zinc oxide can achieve the above goals.
[0011] At present, according to the reported literature, polystyrene microspheres can only be deposited on a flat substrate or synthesized as powdered samples, which greatly limits their use. The traditional synthesis strategies for controllably assembling polystyrene microspheres onto a variety of substrates mainly include vertical deposition self-assembly, electrophoresis, colloidal epitaxy, and natural deposition methods. Among them, the vertical deposition method is widely used because of its advantages such as simple equipment, economy, short preparation cycle, and controllable crystal layer thickness. However, no matter which method is used, polystyrene microspheres are either combined with a flat substrate or synthesized as powder alone, which seriously reduces the specific surface area, flexibility, and mechanical properties of polystyrene microspheres, thereby limiting their application. However, when the substrate is a flexible curved surface such as a substrate, there are no polar groups on the surface of the polystyrene microspheres, so there is no adhesion itself. For the substrate, some places with relatively large curvature cannot provide sufficient support and adhesion, causing the polystyrene microspheres to fall off. Summary of the invention
[0012] The technical problem to be solved by the present invention is to provide a method for depositing polystyrene microspheres to solve the problems of supporting force and adhesion force of polystyrene microspheres deposited in traditional methods, and to provide a method for depositing polystyrene microspheres applicable to a variety of substrates.
[0013] In order to solve the above problems, the present invention provides a method for depositing polystyrene microspheres, comprising the following steps:
[0014] S1: Select substrate: Select the substrate on which the polystyrene microspheres are deposited;
[0015] S2: Atomic layer deposition of zinc oxide film: placing the substrate on the substrate in the reaction chamber of the atomic layer deposition instrument, closing the chamber, evacuating the reaction chamber, making the chamber and the pipeline reach a vacuum state, setting the gas flow and temperature, and starting deposition after the temperature of the reaction chamber is stable: vaporizing diethyl zinc to obtain a diethyl zinc precursor for deposition through the reaction chamber, then stopping the introduction of the diethyl zinc vaporized precursor, and introducing nitrogen purge gas, and introducing the precursor obtained by vaporizing water into the reaction chamber, then stopping the introduction of the water vaporized precursor, and introducing nitrogen purge gas again, repeating the above cycle, so that a zinc oxide film layer is formed on the carbon cloth;
[0016] Preparation of polystyrene microsphere suspension: dispersing polystyrene microsphere dispersion in deionized water, and dispersing under ultrasonic conditions to obtain a dispersed polystyrene microsphere suspension;
[0017] S3: Take the substrate treated in step S2, fix it vertically on the side wall of the container with a polyimide tape, pour the polystyrene microsphere suspension into it, soak the substrate in the polystyrene microsphere suspension, and then place it in a constant temperature oven until the solvent evaporates to obtain a substrate with deposited polystyrene microspheres.
[0018] As a preferred solution, in step S1, the substrate is one of carbon nanotubes, electrospinning membranes, carbon cloth, nickel foam, three-dimensional graphene, 3D printed metals, 3D printed polymers and 3D printed inorganic substances.
[0019] As a preferred solution, in step S2, the conditions for the cabin and pipeline to reach a vacuum state are: the vacuum degree in the cabin is 8-19hPa, and the vacuum degree in the pipeline is 3-5hPa.
[0020] As a preferred solution, in step S2, the gas flow rate of the nitrogen gas is 100-200 sccm, and the conditions for introducing the nitrogen purge gas and introducing the nitrogen purge gas again are: controlling the purge time of the nitrogen gas to be 4-6 s.
[0021] As a preferred solution, in step S2, the purge time of the vaporized diethyl zinc precursor and the vaporized water precursor is 0.1-0.4 s.
[0022] As a preferred solution, in step S2, the diameter of the polystyrene microspheres is 200-500 nm, the volume fraction of the polystyrene microsphere dispersion is 3.5%-5% W / V, and the dosage is 0.3-0.6 ml.
[0023] As a preferred solution, the amount of deionized water used is 14-20 mL; the ultrasonic conditions are: ultrasonic power is 200W-300W, and ultrasonic time is 10min-20min.
[0024] As a preferred solution, in step S2, the cycle is repeated 60-120 times.
[0025] As a preferred solution, in the step S3, when the substrate is immersed in the polystyrene microsphere suspension, the step further includes controlling the upper surface of the substrate to be lower than the liquid surface.
[0026] As a preferred solution, in step S3, the upper surface of the substrate is 0.5 mm-1 mm below the liquid level, and the temperature of the constant temperature oven is 60-80°C.
[0027] The present invention provides a method for depositing polystyrene microspheres, which proposes a method combining atomic layer deposition and vertical deposition to achieve uniform deposition of polystyrene microspheres on a variety of substrates. The deposition method utilizes the strong interaction between zinc oxide and polystyrene spheres, and can deposit polystyrene microspheres uniformly on a curved flexible substrate such as a substrate, even in places with relatively large curvatures, that is, each carbon fiber surface has polystyrene microspheres, and also has excellent mechanical properties and stability.
[0028] The present invention discloses a method for depositing polystyrene microspheres. The method uses an ultra-thin conformal film deposition technology of atomic layer deposition to deposit a zinc oxide film on a substrate woven with carbon fibers to increase the hydrophilicity of the substrate surface. The binding force between zinc oxide and polystyrene microspheres is then used to achieve successful deposition of polystyrene microspheres on the substrate using a vertical deposition method. This method is also considered to be promising for other curved substrates. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The present invention provides a method for depositing polystyrene microspheres, comprising the following steps:
[0031] S1: Select substrate: Select the substrate on which the polystyrene microspheres are deposited;
[0032] S2: Atomic layer deposition of zinc oxide film: the substrate is placed on the substrate in the reaction chamber of the atomic layer deposition instrument, the chamber is closed, the reaction chamber is evacuated, the chamber and the pipeline are in a vacuum state, the gas flow rate and temperature are set, and deposition is started after the temperature of the reaction chamber is stable: the diethyl zinc precursor obtained by vaporizing diethyl zinc is deposited through the reaction chamber, and after the first monolayer film is formed on the substrate (the film layer is sporadic points in the early stage of deposition, and a formed film layer is formed after the number of cycles increases), the introduction of the diethyl zinc vaporized precursor is stopped, and nitrogen purge gas is introduced, and the precursor obtained by water vaporization is introduced into the reaction chamber. After the second monolayer film is formed on the first monolayer film, the introduction of the water vaporized precursor is stopped, and nitrogen purge gas is introduced again, and the above cycle is repeated to form a zinc oxide film layer on the carbon cloth;
[0033] Preparation of polystyrene microsphere suspension: dispersing polystyrene microsphere dispersion in deionized water, and dispersing under ultrasonic conditions to obtain a dispersed polystyrene microsphere suspension;
[0034] S3: Take the substrate treated in step S2, fix it vertically on the side wall of the container with a polyimide tape, pour the polystyrene microsphere suspension into it, soak the substrate in the polystyrene microsphere suspension, and then place it in a constant temperature oven until the solvent evaporates to obtain a substrate with deposited polystyrene microspheres.
[0035] Preferably, in step S1, the substrate is one of carbon nanotubes, electrospinning membranes, carbon cloth, nickel foam, three-dimensional graphene, 3D printed metals, 3D printed polymers and 3D printed inorganic substances.
[0036] Preferably, in step S2, the conditions for the cabin and the pipeline to reach a vacuum state are: the vacuum degree in the cabin is 8-19 hPa, and the vacuum degree in the pipeline is 3-5 hPa.
[0037] Preferably, in step S2, the gas flow rate of the nitrogen gas is 100-200 sccm, and the conditions for introducing the nitrogen purge gas and introducing the nitrogen purge gas again are: controlling the purge time of the nitrogen gas to be 4-6 s.
[0038] Preferably, in step S2, the purge time of the vaporized diethyl zinc precursor and the vaporized water precursor is 0.1-0.4 s.
[0039] Preferably, in step S2, the diameter of the polystyrene microspheres is 200-500 nm, the volume fraction of the polystyrene microsphere dispersion is 3.5%-5% W / V, and the dosage is 0.3-0.6 ml.
[0040] Preferably, the amount of deionized water is 14-20 mL; the ultrasonic conditions are: ultrasonic power is 200W-300W, and ultrasonic time is 10min-20min.
[0041] Preferably, in step S2, the cycle is repeated 60-120 times.
[0042] Preferably, in the step S3, when the substrate is immersed in the polystyrene microsphere suspension, the step further includes controlling the upper surface of the substrate to be below the liquid surface.
[0043] Preferably, in step S3, the upper surface of the substrate is 0.5 mm-1 mm below the liquid level, and the temperature of the constant temperature oven is 60-80°C.
[0044] The above scheme of the present invention is specifically and detailedly developed below in combination with specific substrates, experimental methods and experimental conditions:
[0045] Embodiment 1:
[0046] S1: Select carbon nanotube fiber as substrate: Atomic layer deposition of zinc oxide (ZnO) film on carbon nanotube fiber. Place the carbon nanotube fiber on the substrate in the reaction chamber of the atomic layer deposition instrument, close the chamber, evacuate the reaction chamber, and make the vacuum state of the chamber and pipeline reach 9hPa and 4hPa respectively. Then set the nitrogen gas flow rate to 200sccm and the temperature to 75℃, and start the deposition process after the temperature of the reaction chamber stabilizes for a period of time. First, control the pneumatic valve of the diethylzinc (Zn(C2H5)2) source bottle to open for 0.1s, so that its vaporized precursor passes through the reaction chamber to form the first monolayer film on the carbon nanotube fiber; thereafter, introduce 4s of nitrogen purge gas to effectively remove the excess diethylzinc vaporized precursor and reaction by-products that do not participate in the reaction in the reaction chamber. Next, the pneumatic valve of the water (H2O) source bottle is controlled to open for 0.1s, so that the vaporized precursor is passed into the reaction chamber to form a second monolayer film on the first monolayer film; thereafter, nitrogen purge gas is passed again for 4s to effectively remove the excess water vaporized precursor and reaction byproducts that do not participate in the reaction in the reaction chamber. The above process is one cycle, and the above cycle is repeated 120 times until a zinc oxide film layer of about 20nm is formed on the carbon nanotube fiber;
[0047] Adjust the concentration of monodisperse polystyrene microspheres, take 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm and disperse them in 15 ml of deionized water, and perform ultrasonic dispersion treatment under 200 W ultrasonic conditions for 15 min to obtain a uniformly dispersed polystyrene microsphere suspension;
[0048] S3: Vertical deposition of polystyrene microspheres: The carbon nanotube fibers in S1 are fixed in a beaker by hanging vertically to the bottom of the beaker, and then the polystyrene microsphere suspension evenly dispersed in S2 is poured in, so that the carbon nanotube fibers are completely immersed in the polystyrene microsphere suspension, and the upper surface of the carbon nanotube fibers is 1 mm below the liquid surface, and then placed in a constant temperature oven at 70°C until the solvent evaporates to obtain carbon nanotube fibers with deposited polystyrene microspheres.
[0049] Embodiment 2:
[0050] S1: Select an electrospinning membrane as a substrate: Take 1g of polyacrylonitrile (PAN) and dissolve it in 10ml of N,N-dimethylformamide (DMF), and then stir it for 18h; then transfer the obtained solution to the electrospinning syringe, set the spinning parameters, voltage 12kV, distance between the needle and the collector is 10cm, syringe propulsion rate 0.5ml / h, until the solution remains 1ml, stop spinning, remove the spun film from the collector, and cut it into a specification of 1×4cm.
[0051] S2: Atomic layer deposition of zinc oxide (ZnO) thin film on the electrospun membrane obtained in S1: Place the electrospun membrane on the substrate in the reaction chamber of the atomic layer deposition instrument, close the chamber, evacuate the reaction chamber, and make the vacuum state of the chamber and pipeline reach 9hPa and 4hPa respectively. Then set the nitrogen gas flow rate to 200sccm and the temperature to 75℃. After the temperature of the reaction chamber is stabilized for a period of time, start the deposition process: First, control the pneumatic valve of the diethyl zinc (Zn(C2H5)2) source bottle to open for 0.1s to vaporize the precursor The liquid passes through the reaction chamber to form the first monolayer on the electrospun membrane; thereafter, a nitrogen purge gas is introduced for 4 seconds to effectively remove the excess diethylzinc vaporized precursor and reaction byproducts that do not participate in the reaction in the reaction chamber; then, the pneumatic valve of the water (H2O) source bottle is controlled to open for 0.1 seconds to allow its vaporized precursor to pass into the reaction chamber to form the second monolayer on the first monolayer; thereafter, a nitrogen purge gas is introduced again for 4 seconds to effectively remove the excess water vaporized precursor and reaction byproducts that do not participate in the reaction in the reaction chamber. The above process is one cycle, and the above cycle is repeated 90 times until a zinc oxide film layer of about 15nm is formed on the electrospun membrane;
[0052] 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm were dispersed in 15 ml of deionized water, and then subjected to ultrasonic treatment at 200 W for 15 min to obtain a uniformly dispersed polystyrene microsphere suspension.
[0053] S3: Fix the electrospun membrane in S2 vertically on the wall of the beaker with polyimide (PI) tape, and then pour the evenly dispersed polystyrene microsphere suspension in S2 into it, so that the electrospun membrane is completely immersed in the polystyrene microsphere suspension, and the upper surface of the electrospun membrane is 1 mm below the liquid surface, and then place it in a constant temperature oven at 70°C until the solvent evaporates to obtain an electrospun membrane with deposited polystyrene microspheres.
[0054] Embodiment three:
[0055] S1: Select carbon cloth as the substrate, and deposit zinc oxide film on the surface of the carbon cloth. Place 1×4cm carbon cloth in beakers containing acetone and deionized water, respectively, and wash it by ultrasonic for 15 minutes. Then place the carbon cloth in a 60℃ constant temperature oven to dry overnight;
[0056] S2: Atomic layer deposition of zinc oxide (ZnO) film on the obtained substrate: Place the carbon cloth on the substrate in the reaction chamber of the atomic layer deposition instrument, close the chamber, evacuate the reaction chamber, and make the chamber and pipeline reach a vacuum state of 9hPa and 4hPa respectively. Then set the nitrogen gas flow rate to 200sccm and the temperature to 75℃, and start the deposition process after the temperature of the reaction chamber is stabilized for a period of time: First, control the pneumatic valve of the diethyl zinc (Zn(C2H5)2) source bottle to open for 0.1s, so that its vaporized precursor passes through the reaction chamber to form the first monolayer film on the carbon cloth. Thereafter, introduce 4s of nitrogen purge gas to effectively remove the excess diethyl zinc vaporized precursor and reaction by-products that do not participate in the reaction in the reaction chamber. Then, control the pneumatic valve of the water (H2O) source bottle to open for 0.1s, so that its vaporized precursor passes into the reaction chamber, and the second monolayer film is formed on the first monolayer film. After that, nitrogen purge gas was introduced again for 4s to effectively remove the excess water vaporized precursor and reaction byproducts that did not participate in the reaction in the reaction chamber. The above process is one cycle, and the above cycle is repeated 120 times until a zinc oxide film layer of about 20nm is formed on the carbon cloth;
[0057] 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm were dispersed in 15 ml of deionized water, and then subjected to ultrasonic treatment at 200 W for 15 min to obtain a uniformly dispersed polystyrene microsphere suspension.
[0058] S3: Fix the carbon cloth treated with S2 vertically on the wall of the beaker with polyimide (PI) tape, and then pour the polystyrene microsphere suspension evenly dispersed in S2 into it, so that the substrate is completely immersed in the polystyrene microsphere suspension and the upper surface of the substrate is 1 mm below the liquid surface. Then, place it in a constant temperature oven at 70°C until the solvent evaporates to obtain a substrate with deposited polystyrene microspheres.
[0059] Embodiment 4:
[0060] S1: Select nickel foam as a substrate, and perform atomic layer deposition of zinc oxide (ZnO) thin film on the nickel foam: Use a tablet press to compress the nickel foam to 0.3 cm;
[0061] S2: Then, the nickel foam is placed on the substrate in the reaction chamber of the atomic layer deposition instrument, the chamber is closed, and the reaction chamber is evacuated to make the chamber and the pipeline reach a vacuum state of 9hPa and 4hPa respectively. Then, the nitrogen gas flow rate is set to 200sccm and the temperature is 75℃. After the temperature of the reaction chamber is stabilized for a period of time, the deposition process is started: first, the pneumatic valve of the diethyl zinc (Zn(C2H5)2) source bottle is controlled to open for 0.1s, so that its vaporized precursor passes through the reaction chamber to form the first monolayer film on the nickel foam; thereafter, 4s of nitrogen purge gas is introduced to effectively remove the excess diethyl zinc vaporized precursor and reaction by-products that do not participate in the reaction in the reaction chamber; then, the pneumatic valve of the water (H2O) source bottle is controlled to open for 0.1s, so that its vaporized precursor passes into the reaction chamber to form a second monolayer film on the first monolayer film; thereafter, 4s of nitrogen purge gas is introduced again to effectively remove the excess water vaporized precursor and reaction by-products that do not participate in the reaction in the reaction chamber. The above process is one cycle, and the above cycle is repeated 120 times until a zinc oxide film layer of about 20 nm is formed on the nickel foam;
[0062] : Adjust the concentration of monodisperse polystyrene microspheres. Take 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm and disperse them in 15 ml of deionized water, and perform ultrasonic dispersion treatment under 200 W ultrasonic conditions for 15 min to obtain a uniformly dispersed polystyrene microsphere suspension;
[0063] S3: Vertical deposition of polystyrene microspheres. The nickel foam in S2 was fixed to the wall of the beaker with polyimide tape, and then the polystyrene microsphere suspension evenly dispersed in S2 was poured in, so that the nickel foam was completely immersed in the polystyrene microsphere suspension, and the upper surface of the nickel foam was 1mm below the liquid surface, and then placed in a 70°C constant temperature oven until the solvent evaporated to obtain a nickel foam with deposited polystyrene microspheres.
[0064] Embodiment five:
[0065] S1: Preparation of three-dimensional graphene as substrate: First, prepare silicon dioxide (SiO2) gyroid structural foam to assist in the preparation of three-dimensional graphene: First, mix and stir silicon dioxide powder, photocurable resin, diphenyl-(2,4,6-trimethylbenzoyl)oxyphosphorescent initiator and modifier Variquat CC 42NS, and then print 270×10×2mm by Asiga MAX 27UV printing (ultraviolet light source is 385nm, layer resolution is 27μm) 3. The printed silica gyroid structure was then annealed at 1350 degrees Celsius for 5 hours. Next, the silica template was heated to 1000 degrees Celsius in a chemical deposition furnace for one hour, after which ethanol bubbled with argon was introduced into the quartz tube and heated at 1000 degrees Celsius for another 0.5 hours. After cooling to room temperature, the entire sample was immersed in hydrofluoric acid (HF) overnight to remove the silica template and obtain a three-dimensional graphene substrate.
[0066] S2: Atomic layer deposition of zinc oxide (ZnO) film on three-dimensional graphene. Then, the three-dimensional graphene is placed on the substrate in the reaction chamber of the atomic layer deposition instrument, the chamber is closed, and the reaction chamber is evacuated to make the chamber and the pipeline reach a vacuum state. Then, the gas flow rate and temperature are set, and the deposition process is started after the temperature of the reaction chamber is stabilized for a period of time: first, the diethyl zinc (Zn (C2H5) 2) vaporized precursor passes through the reaction chamber to form a first monolayer film on the three-dimensional graphene; thereafter, the diethyl zinc vaporized precursor is stopped from entering, and nitrogen purge gas is introduced to effectively remove the excess diethyl zinc vaporized precursor and reaction by-products that do not participate in the reaction in the reaction chamber; then, water (H2O) vaporized precursor is introduced into the reaction chamber to form a second monolayer film on the first monolayer film. Thereafter, the water vaporized precursor is stopped from entering, and nitrogen purge gas is introduced to effectively remove the excess water vaporized precursor and reaction by-products that do not participate in the reaction in the reaction chamber. The above process is a cycle, and the above cycle is repeated until a zinc oxide film layer with a desired thickness is formed on the three-dimensional graphene;
[0067] A certain amount of monodisperse polystyrene microspheres are dispersed in deionized water and dispersed under ultrasonic conditions to obtain a uniformly dispersed polystyrene microsphere suspension;
[0068] S3: Fix the three-dimensional graphene in S2 on the wall of the beaker with polyimide tape, and then pour in a uniformly dispersed polystyrene microsphere suspension so that the three-dimensional graphene is completely immersed in the polystyrene microsphere suspension and the upper surface of the three-dimensional graphene is lower than the liquid surface. Then, place it in a constant temperature oven and let it stand until the solvent evaporates to obtain three-dimensional graphene with deposited polystyrene microspheres.
[0069] Embodiment six:
[0070] S1: Prepare nickel as substrate for 3D printing: Take 40g nickel sulfate (NiSO4) powder, 5ml Variquat CC 42NS and 30ml light-curable resin, stir at room temperature for 2h, and grind with a ball mill. The obtained resin is printed by Asiga Max X27 UV-printer, select Primitive structure, sintered at 500℃ in a muffle furnace for 4h, and the obtained nickel oxide substrate is reduced at 600℃ in argon hydrogen atmosphere for 5h to obtain a nickel substrate.
[0071] S2: Atomic layer deposition of zinc oxide (ZnO) thin film on 3D printed nickel substrate. The 3D-printed nickel substrate was placed on the substrate in the reaction chamber of the atomic layer deposition instrument, the chamber was closed, and the reaction chamber was evacuated to make the chamber and the pipeline reach a vacuum state of 9hPa and 4hPa respectively; then the nitrogen gas flow rate was set to 200sccm and the temperature was 75°C, and the deposition process was started after the temperature of the reaction chamber was stabilized for a period of time: first, the pneumatic valve of the diethylzinc (Zn(C2H5)2) source bottle was controlled to open for 0.1s, so that its vaporized precursor passed through the reaction chamber to form a first monolayer film on the 3D-printed nickel substrate; thereafter, 4s of nitrogen purge gas was introduced to effectively remove the excess diethylzinc vaporized precursor and reaction by-products that did not participate in the reaction in the reaction chamber; then, the pneumatic valve of the water (H2O) source bottle was controlled to open for 0.1s, so that its vaporized precursor passed into the reaction chamber to form a second monolayer film on the first monolayer film; thereafter, 4s of nitrogen purge gas was introduced again to effectively remove the excess water vaporized precursor and reaction by-products that did not participate in the reaction in the reaction chamber. The above process is one cycle, and the above cycle is repeated 120 times until a zinc oxide film layer of about 20 nm is formed on the 3D printed nickel substrate;
[0072] Adjust the concentration of monodisperse polystyrene microspheres: Disperse 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm in 15 ml of deionized water, and perform ultrasonic treatment for 15 min at 200 W to obtain a uniformly dispersed polystyrene microsphere suspension;
[0073] S3: Vertical deposition of polystyrene microspheres: The 3D printed nickel substrate in S2 was fixed to the wall of the beaker with polyimide tape, and then the evenly dispersed polystyrene microsphere suspension in S2 was poured in, so that the 3D printed nickel substrate was completely immersed in the polystyrene microsphere suspension, and the upper surface of the 3D printed nickel substrate was 1 mm below the liquid surface, and then placed in a constant temperature oven at 70°C until the solvent evaporated to obtain a 3D printed nickel substrate with deposited polystyrene microspheres.
[0074] Embodiment seven:
[0075] S1: Prepare 3D printing polymer as substrate: Take 40ml of commercial resin and print it with Asiga Max X27UV–printer, choose negative Poisson structure, and the thickness is 0.2cm.
[0076] S2: 3D printed polymer for atomic layer deposition of zinc oxide (ZnO) film: The 3D printed polymer is placed on the substrate in the reaction chamber of the atomic layer deposition instrument, the chamber is closed, and the reaction chamber is evacuated to a vacuum state of 9hPa and 4hPa in the chamber and pipeline respectively; then the nitrogen gas flow rate is set to 200sccm and the temperature is set to 75°C, and the deposition process is started after the reaction chamber temperature is stabilized for a period of time: first, the pneumatic valve of the diethyl zinc (Zn(C2H5)2) source bottle is controlled to open for 0.1s, so that its vaporized precursor passes through the reaction chamber to form the first monolayer film on the 3D printed polymer; thereafter , a nitrogen purge gas is introduced for 4s to effectively remove the excess diethylzinc vaporized precursor and reaction byproducts that do not participate in the reaction in the reaction chamber; then, the pneumatic valve of the water (H2O) source bottle is controlled to open for 0.1s to allow its vaporized precursor to enter the reaction chamber to form a second monolayer film on the first monolayer film; thereafter, a nitrogen purge gas is introduced for 4s again to effectively remove the excess water vaporized precursor and reaction byproducts that do not participate in the reaction in the reaction chamber; the above process is one cycle, and the above cycle is repeated 120 times until a zinc oxide film layer of about 20nm is formed on the 3D printed polymer;
[0077] Adjust the concentration of monodisperse polystyrene microspheres: Disperse 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm in 15 ml of deionized water, and perform ultrasonic treatment for 15 min at 200 W to obtain a uniformly dispersed polystyrene microsphere suspension;
[0078] S4: Vertical deposition of polystyrene microspheres: The 3D printed polymer in S2 was fixed to the wall of the beaker with polyimide tape, and then the polystyrene microsphere suspension evenly dispersed in S2 was poured in, so that the 3D printed polymer was completely immersed in the polystyrene microsphere suspension, and the upper surface of the 3D printed polymer was 1 mm below the liquid surface, and then placed in a constant temperature oven at 70°C until the solvent evaporated to obtain a 3D printed polymer with deposited polystyrene microspheres.
[0079] Embodiment eight:
[0080] S1: Prepare inorganic materials as substrate: First, prepare the silicon dioxide (SiO2) gyroid structure. First, mix the silicon dioxide powder, photocurable resin, diphenyl-(2,4,6-trimethylbenzoyl)oxyphosphorescent initiator and modifier Variquat CC42NS, and then print a 270×10×2mm gyroid structure using Asiga MAX 27UV printer (ultraviolet light source: 385nm, layer resolution: 27μm). 3 The printed template was then annealed at 1350 degrees Celsius for 5 hours.
[0081] S2: 3D printed inorganic substrate for atomic layer deposition of zinc oxide (ZnO) film: Place the 3D printed inorganic substrate on the substrate in the reaction chamber of the atomic layer deposition instrument, close the chamber, evacuate the reaction chamber, and make the vacuum state of the chamber and pipeline reach 9hPa and 4hPa respectively; then set the nitrogen gas flow rate to 200sccm and the temperature to 75℃, and start the deposition process after the reaction chamber temperature stabilizes for a period of time: first, control the pneumatic valve of the diethylzinc (Zn(C2H5)2) source bottle to open for 0.1s, so that its vaporized precursor passes through the reaction chamber to form the first monolayer film on the 3D printed polymer. Thereafter, nitrogen purge gas is introduced for 4 seconds to effectively remove the excess vaporized diethyl zinc precursor and reaction byproducts that do not participate in the reaction in the reaction chamber; then, the pneumatic valve of the water (H2O) source bottle is controlled to open for 0.1 seconds to allow its vaporized precursor to enter the reaction chamber, forming a second monolayer film on the first monolayer film; thereafter, nitrogen purge gas is introduced again for 4 seconds to effectively remove the excess vaporized water precursor and reaction byproducts that do not participate in the reaction in the reaction chamber; the above process is one cycle, and the above cycle is repeated 120 times until a zinc oxide film layer of about 20 nm is formed on the 3D printed inorganic substrate;
[0082] Adjust the concentration of monodisperse polystyrene microspheres. Disperse 0.5 ml of 5% W / V monodisperse polystyrene microspheres with a diameter of 245 nm in 15 ml of deionized water, and perform ultrasonic treatment for 15 min at 200 W to obtain a uniformly dispersed polystyrene microsphere suspension.
[0083] S3: Vertical deposition of polystyrene microspheres. The 3D printed inorganic substrate in S2 was fixed to the wall of the beaker with polyimide tape, and then the evenly dispersed polystyrene microsphere suspension in S2 was poured in, so that the 3D printed polymer was completely immersed in the polystyrene microsphere suspension, and the upper surface of the 3D printed polymer was 1 mm below the liquid surface, and then placed in a 70°C constant temperature oven until the solvent evaporated to obtain a 3D printed polymer with deposited polystyrene microspheres.
[0084] In order to make up for the shortcomings of the prior art, the present invention proposes a method combining the above-mentioned atomic layer deposition with vertical deposition to achieve uniform deposition of polystyrene microspheres on a variety of substrates, and the surface of the substrate is modified by atomic layer deposition of zinc oxide. This modification is plated on the substrate layer by layer in the form of a single atomic film, and is carried out at a low temperature without destroying the structure and morphology of the substrate. The main purpose of the modification is to improve the hydrophilicity of the substrate to ensure the formation of a meniscus during the vertical deposition process, as well as the binding force between the substrate and the polystyrene microspheres to overcome the shedding of polystyrene microspheres on surfaces with large curvature during the vertical deposition process. Practice has shown that this modification method can achieve uniform deposition of polystyrene microspheres on the substrate.
[0085] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.
Claims
1. A method for depositing polystyrene microspheres, characterized in that: The following steps are involved: S1: Select substrate: Select the substrate on which the polystyrene microspheres are deposited; S2: Atomic layer deposition of zinc oxide film: placing the substrate on the substrate in the reaction chamber of the atomic layer deposition instrument, closing the chamber, evacuating the reaction chamber, making the chamber and the pipeline reach a vacuum state, setting the gas flow and temperature, and starting deposition after the temperature of the reaction chamber is stable: vaporizing diethyl zinc to obtain a diethyl zinc precursor and depositing it through the reaction chamber, then stopping the introduction of the diethyl zinc precursor, and introducing nitrogen purge gas, and introducing the precursor obtained by water vaporization into the reaction chamber for further deposition, then stopping the introduction of the water vaporized precursor, and introducing nitrogen purge gas again, and repeating the above cycle until a zinc oxide film layer is formed on the carbon cloth; Preparation of polystyrene microsphere suspension: dispersing polystyrene microsphere dispersion in deionized water, and dispersing under ultrasonic conditions to obtain a dispersed polystyrene microsphere suspension; S3: Take the substrate treated in step S2, fix it vertically on the side wall of the container with a polyimide tape, pour the polystyrene microsphere suspension into it, soak the substrate in the polystyrene microsphere suspension, and then place it in a constant temperature oven until the solvent evaporates to obtain a substrate with deposited polystyrene microspheres.
2. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In the step S1, the substrate is one of carbon nanotubes, electrospinning membranes, carbon cloth, nickel foam, three-dimensional graphene, 3D printed polymers and 3D printed inorganic substances.
3. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In step S2, the conditions for the cabin and the pipeline to reach a vacuum state are: the vacuum degree in the cabin is 8-19 hPa, and the vacuum degree in the pipeline is 3-5 hPa.
4. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In the step S2, the gas flow rate of the nitrogen gas is 100-200 sccm, and the conditions for introducing the nitrogen purge gas and introducing the nitrogen purge gas again are: controlling the purge time of the nitrogen gas to be 4-6 s.
5. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In the step S2, the purge time of the diethyl zinc precursor and the water vaporization precursor is 0.1-0.4 s.
6. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In the step S2, the diameter of the polystyrene microspheres is 200-500 nm, the volume fraction of the polystyrene microsphere dispersion is 3.5%-5% W / V, and the dosage is 0.3-0.6 ml.
7. The method for depositing polystyrene microspheres according to claim 6, characterized in that: The amount of deionized water used is 14-20 mL; the ultrasonic conditions are: ultrasonic power is 200W-300W, and ultrasonic time is 10min-20min.
8. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In step S2, the cycle is repeated 60-120 times.
9. The method for depositing polystyrene microspheres according to claim 1, characterized in that: In the step S3, when the substrate is immersed in the polystyrene microsphere suspension, the operation of controlling the upper surface of the substrate to be lower than the liquid surface is also included.
10. The method for depositing polystyrene microspheres according to claim 9, characterized in that: In the step S3, the upper surface of the substrate is 0.5-1 mm below the liquid surface, and the temperature of the constant temperature oven is 60-80°C.
